2005
DOI: 10.1243/095441005x7259
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Damage-Tolerant Flight Control System

Abstract: The performance and stability requirements for a robust flight control system design are presented in the form of a 'design challenge.' The challenge includes description of specific vehicle failures that are to be accommodated by the flight control system. The vehicle chosen for the design is the innovative control effector vehicle, and both longitudinal and lateral/directional degrees of freedom are included. Two flight conditions are considered: Mach number 0.3 and altitude 15 000 ft; Mach number 0.9 and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…7 They found that damaged aircraft experience abrupt and violent changes of their aerodynamics as well as physical characteristics such as weight, center of gravity (CG), and moment of inertia (MOI); therefore, understanding the effects of aircraft damage on the flight dynamic characteristics is crucial for designing a damage-tolerant control system. 8,9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 They found that damaged aircraft experience abrupt and violent changes of their aerodynamics as well as physical characteristics such as weight, center of gravity (CG), and moment of inertia (MOI); therefore, understanding the effects of aircraft damage on the flight dynamic characteristics is crucial for designing a damage-tolerant control system. 8,9…”
Section: Introductionmentioning
confidence: 99%
“…7 They found that damaged aircraft experience abrupt and violent changes of their aerodynamics as well as physical characteristics such as weight, center of gravity (CG), and moment of inertia (MOI); therefore, understanding the effects of aircraft damage on the flight dynamic characteristics is crucial for designing a damage-tolerant control system. 8,9 Kim and Calise proposed neural network-based adaptive flight controller in 1997. 10 They designed a flight control architecture based on feedback linearization of aircraft dynamics so that neural networks adaptive term can compensate for model inversion error.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the effects of the aircraft's damage on the flight dynamic characteristics is crucial for designing a damage-tolerant control system. 10,11 Nguyen et al 12,13 constructed a six degree-of-freedom model that depicts the conventional transport aircraft with a damaged wing. They also designed the adaptive flight control system for this damaged aircraft model using neural network.…”
Section: Introductionmentioning
confidence: 99%
“…Shtessel et al [6] propose reconfigurable sliding mode control with direct adaptation. Hess et al [7] use sliding mode control with asymptotic observers.…”
Section: Introductionmentioning
confidence: 99%